1971
DOI: 10.1111/j.1432-1033.1971.tb19678.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Angiotensin‐II Conformations by Circular Dichroism

Abstract: Angiotensinamide I1 has been studied by circular-dichroism spectroscopy in comparison with some of its peptidic fragments and structural analogs. The following observations have been made. The stepwise examination of elongated peptides shows the appearance of a structural organisation at the heptapeptide stage. Evidence that C-terminal phenylalanine residue plays an important role on the overall conformation of the octapeptide is obtained. As already suggested for some other short peptides, circular-dichroism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0
1

Year Published

1972
1972
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 18 publications
4
33
0
1
Order By: Relevance
“…If i t would be so in trifluoroethanol, the C-terminal heptapeptide should present a negative band around 220nm and this is not the case. Thus part of the negative band a t 220nm presented by the decapeptide would better correspond to chromophore interactions of the type of antiparallel ,9-structures [20,23,24]. Hence the presence of the shoulder a t 206nm and the intense band a t 220nm, suggest that a t least two types of peptidic chromophore interactions participate in the ordered conformation of the decapeptide.…”
Section: Organic Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…If i t would be so in trifluoroethanol, the C-terminal heptapeptide should present a negative band around 220nm and this is not the case. Thus part of the negative band a t 220nm presented by the decapeptide would better correspond to chromophore interactions of the type of antiparallel ,9-structures [20,23,24]. Hence the presence of the shoulder a t 206nm and the intense band a t 220nm, suggest that a t least two types of peptidic chromophore interactions participate in the ordered conformation of the decapeptide.…”
Section: Organic Solutionsmentioning
confidence: 99%
“…It was of interest to investigate whether an increase in temperature would shift the balance between the existing conformations, as observed in other instances [20]. Fig.3 reports experiments carried out a t pH 7.4 between Fig.…”
Section: Aqueous Solutions At Different Temperaturesmentioning
confidence: 99%
“…Organic solvents like trifluoroethanol, alkaline methanol or ethanol promoted a considerable structuration of the dissolved angiotensinamide 1 1 into a predominant form, which, by circular dichroism measurements, has been tentatively assigned as a cross /? structure [6], defined according to Pysh [7] and Timasheff et al [S]. The required folding of the molecule was assigned principally to the hydrophobic interactions between the 3 and 5 valine and the 8 phenylalanine side-chains and to the cis conformation of the histidine-proline peptide bond.…”
mentioning
confidence: 99%
“…Fermandjian et al (23) suggested that a conformational change observed by circular dichroism upon heating angiotensin II at pH 6 was attributable to trans-to-cis isomerization of proline. A later report from this group (24) signed a major circular dichroism change observed upon titration through pH 6.5 to reorientation of the tyrosine side chain rather than a backbone conformational change.…”
mentioning
confidence: 99%